Extension of vase life of cut orchids using ozonated water and 1-methylycyclopropene - Almasi, Parviz (2013)
Orchid industry has a particular situation within ornamental plants in Malaysia. As, 46% of total floriculture industry was occupied by orchid flowers in 2011. Most cut orchid flowers are ethylene sensitive in the spite of having acceptable longevity and postharvest life. When they are packed for export they show ethylene injury symptoms such as bud and floret abscission and short vase life. 1-MCP can control ethylene production and action and probably reduces the ethylene sensitivity. Another possible reason for the short span life may be microbial blockage in xylem conduits. Aqueous ozone can be a good candidate for improving the water conductivity in cut stems by its microbial growth inhibition effect. 1-mythylcyclopropane (1-MCP) and aqueous ozone were used for controlling ethylene sensitivity and inhibition of xylem blockage in two ethylene-sensitive cut orchids, Dendrobium ‘Darren Glory’ and Mokara ‘Calypso Jumbo’. Three experiments were conducted at Department of Crop science, Faculty of Agriculture, Universiti Putra Malaysia (UPM), Serdang, Selangor Darul Ehsan. In experiment one, inflorescences of 12 cut orchid hybrids consisted of six cut Dendrobium hybrids (Dendrobium ‘Darren Glory’, D. ‘Sonia Red’, D. ‘Sonia White’, D. ‘Sonia Bom’, D. ‘Shavin White’ and D. ‘Jacqueline Concert’ x D. ‘Rinappa’) and six Mokara hybrids (Mokara ‘Calypso Jumbo’, M. ‘Chao Praya Classic’, M. ‘Citi Gold’, M. ‘ Boy Blue’, M. ‘Red’ and M. ‘Chak Kuan Blue’) were determined for their ethylene sensitivity levels. Inflorescences were treated with 0 and 10 μL/L ethylene gas for 24 hours in 79 L chambers. The chambers were aerated and stems of flowers were trimmed and placed in PE bags containing vase solution [dіstіllеd water + 250 mg/L 8-hydroxyquіnolіnе cіtrаtе (8-HQC) + 150 mg/L citric аcіd + 4% sucrose, pH=3.5]. Weight loss, vase life, ethylene production and anthocyanin content and expression of ACC synthase and ACC oxidase genes of florets were determined. Results showed that exposure to ethylene caused reduction of vase life tremendously. This was manifested by epinasty, premature wilting and abscission in florets and buds for all hybrids. Weight loss and anthocyanin degradations increased when flowers were exposed to ethylene. After exposure to ethylene, higher expressions of both ACS and ACO genes were found in fully open florets. However, different hybrids showed distinct responses to ethylene sensitivities and degrees of deterioration. Therefore, they can be categorized into two groups, sensitive and less sensitive. Dendrobium ‘Darren Glory’, D. ‘Jaquelyne Concert’ x D. ‘Rinappa’, Mokara ‘Calypso Jumbo’, M. ‘Chаo Prаyа Clаssіc’(MCPC) and M. ‘Red’ exhibited the utmost epinasty, weight loss and anthocyanin content degradation in sepals and petals thus, can be considered as sensitive group while the rest were less sensitive. In the second experiment, the inflorescences of two very sensitive (Dendrobium ‘Darren Glory’ and Mokara ‘Calypso Jumbo’) and two less sensitive (D. ‘Sonia Bom’ and M. ‘Citi Gold’) hybrids that were determined in experiment first, were studied. Inflorescences were divided into two groups and placed in two 79 L chambers. For fumigation of 0 and 300 nL/L 1-MCP, a small vial containing 37.92 mg Ethylbloc was taped to the one chamber’s internal wall. Then, 190 μL/L deionized water was added to the vial. Both chambers were immediately sealed for 4 hours. Then inflorescences of each chamber divided into two subgroups and after labeling the four 39.5 L chambers inflorescences were placed inside them gently. The chambers were hermetically-sealed. Then, two separate 1μL/L ethylene gas, balanced with nitrogen, were injected into the one chamber of each subgroup. After 24 hours the chambers were opened and each inflorescence’s basal stem was trimmed to 12 cm from the first open floret. Then, each inflorescence was placed in the bottle with а cylіndrіcаl polyethylene bag containing 60 ml distilled water and kept in the laboratory at means temperature, relative humidity and light intensity of 25 oC, 78% and 6.57 μmol/m2/s, respectively. The results showed that weight loss in all four hybrids after 1-MCP fumigation even with exogenous ethylene treatment remarkably declined except MCG which did not show any variation to the responses of all treatments. Vase life responses of highly sensitive and less sensitive hybrids to the 1-MCP were positive but almost different. Maximum vase life extension was observed in highly sensitive hybrid (MCJ) about 59% with 300 nL/L 1-MCP treatment and minimum extension was occurred in less sensitive hybrid (MCG) around 39%. So it can be suggested that the effectiveness of 1-MCP on the control of ethylene sensitivity in highly sensitive hybrids was more. In the third experiment, effects of 1-MCP and aqueous ozone on postharvest quality of two very sensitive cut flowers; Dendrobium ‘Darren Glory’ and Mokara ‘Calypso Jumbo’ were studied. The inflorescences were treated with 0 and 300 nL/L 1-MCP. After four hours, the chambers were aerated and the stems were trimmed to 12 cm from the basal end of the first open floret. Each inflorescence was put into a bottle containing 250 mL of distilled water (control treatment) and 5.2 mg/L aqueous ozone.Ethylene production, microbial growth, bud opening, 1-aminocyclopropan oxidase activity (ACO) and vase life were measured. Results showed 1-MeCP can control the ethylene production within 5 day after harvest in both studied cut orchids very well and also ethylene production and ACO activity in D. ‘Darren Glory’ was higher than M. ‘Calypso Jumbo’. Aqueous ozone (5.2 mg/L) declined microbial (bacteria, fungi and yeast) growth when it used as the vase solution and every 24 hours replenished and consequently it was effective on decreasing xylem blockage and the micro-graphs from the xylem showed it clearly. In the forth experiment effects of 4 concentrations of 1-MCP and optimum concentration of aqueous ozone on postharvest quality of sensitive cut flower; Mokara ‘Calypso Jumbo’ were studied. The inflorescences were fumigated with 0, 100, 200, 300 and 400 nL/L 1-MCP. After four hours fumigation, the stems were trimmed to 12 cm from the basal end of the first open floret. First 30 inflorescences with and without 1- MCP fumigation were cut with scalpel into two parts: one had only buds and another one had only open florets. Stem ends were placed in distilled water and ozonized water and then used for ACC content and ACC oxidase activity measurements. Remaining fifty intact inflorescences were placed into the bottles each one, containing 250 mL of distilled water or 3.9 mg/L aqueous ozone based on the combination treatments. Ozonized water was renewed at every 24 hours, but for the rest treatments, vase water was not changed until end of vase life. The results showed that fumigation of the cut Mokara ‘Calypso Jumbo’ flowers with 100 nL/L 1-MCP, followed by using 3.9 mg/L aqueous ozone as the vase water could be recommended as the best postharvest treatments to maintain quality and extend vase life of MCJ orchid hybrids. In addition, these treatments for MCJ were very effective in extending vase live, increasing water uptake and percentage bud opening and also controlling the bacterial growth in vascular system Therefore, optimum postharvest treatments for the cut orchid flowers depended on hybrids. Pretreatment of the cut orchid flowers with 100-300 nL/L 1-MCP, followed by using 3.9 mg/L aqueous ozone as the vase solution could be recommended as the optimum postharvest treatments to maintain quality and extend vase life of both the DDG and MCJ orchid hybrids. In addition, 1-MCP pretreatment for MCJ was very effective in extending vase lives and increasing percentage bud opening. Additionally, aqueous ozone can effectively decreased number of bacteria in vase water and vascular vessels. Another important finding of this experiment was the cause of short vase life in the two cut orchid hybrids. The main reason for the short vase life was due to ethylene sensitivity of the cut flowers and not due to xylem blockage.